Only the largest terrestrial carnivores increase their dietary breadth with increasing prey richness - Ferretti, Francesco; Lovari, Sandro; Lucherini, Mauro; Hayward, Matt W.; Stephens, Philip A. (Mammal Review, 2021)
Animals should adapt their foraging habits, changing their dietary breadth in response to variation in the richness and availability of food resources. Understanding how species modify their dietary breadth according to variation in resource richness would support predictions of their responses to environmental changes that alter prey communities. We evaluated relationships between the dietary breadth of large terrestrial carnivores and the local richness of large prey (defined as the number of species). We tested alternative predictions suggested by ecological and evolutionary theories: with increasing prey richness, species would (1) show a more diverse diet, thus broadening their dietary breadth, or (2) narrow their dietary breadth, indicating specialisation on a smaller number of prey. We collated data from 505 studies of the diets of 12 species of large terrestrial mammalian carnivores to model relationships between two indices of dietary breadth and local prey richness. For the majority of species, we found no evidence for narrowing dietary breadth (i.e. increased specialisation) with increasing prey richness. Although the snow leopard and the dhole appeared to use a lower number of large prey species with increasing prey richness, larger sample sizes are needed to support this result. With increasing prey richness, the five largest carnivores (puma Puma concolor, spotted hyaena Crocuta crocuta, jaguar Panthera onca, lion Panthera leo, and tiger Panthera tigris), plus the Eurasian lynx Lynx lynx and the grey wolf Canis lupus (which are usually top predators in the areas from which data were obtained), showed greater dietary breadth and/or used a greater number of large prey species (i.e. increased generalism). We suggest that dominant large carnivores encounter little competition in expanding their dietary breadth with increasing prey richness; conversely, the dietary niche of subordinate large carnivores is limited by competition with larger, dominant predators. We suggest that, over evolutionary time, ...